Scientific writing 2.0 : a reader and writer's guide - Lebrun, Jean-Luc (World Scientific, 2011)
Helps scientists write papers for scientific journals. Using the key parts of typical scientific papers (Title, Abstract, Introduction, Visuals, Structure, and Conclusions), this title shows through numerous examples, how to achieve the useful qualities required in scientific writing